Performance of Insurance Brokerage Firms: The Role of Insurance Process Innovation as an Entrepreneurial Innovation - Mira, Gerald Kariithi; Ngugi, Karanja; Nyang’au, Samson (Journal Integration of Social Studies and Business Development, 2024)
This study investigates the impact of process innovation as a form of entrepreneurial innovation on the performance of insurance brokerage firms in Kenya. The research is set against the backdrop of persistent underperformance in the sector despite the critical role these firms play in promoting insurance penetration. The inability to enhance process efficiency has been identified as a key factor contributing to their poor performance. Grounded in the diffusion of innovation theory, the study employed a cross-sectional descriptive research design, surveying all 216 insurance brokerage firms in Kenya through a census approach. Data was collected via questionnaires and analyzed using both quantitative (descriptive and inferential statistics) and qualitative (content analysis) methods, with SPSS software used for the quantitative analysis. The findings indicate that process innovation has a significant and positive influence on the performance of these firms. The study concludes that many insurance brokerage firms fail to fully embrace process innovation, resulting in inefficiencies that hinder their operational performance and long-term success.